Comprehensive risk profiles of family history and lifestyle and metabolic risk factors in relation to diabetes: A prospective cohort study. Issue 6 (28th June 2022) - Ye, Chaojie; Wang, Yiying; Kong, Lijie; Zhao, Zhiyun; Li, Mian; Xu, Yu; Xu, Min; Lu, Jieli; Wang, Shuangyuan; Lin, Hong; Chen, Yuhong; Wang, Weiqing; et al.
Abstract: Background: Family history of diabetes, unhealthy lifestyles, and metabolic disorders are individually associated with higher risk of diabetes, but how different combinations of the three risk categories are associated with incident diabetes remains unclear. We aimed to estimate the associations of comprehensive risk profiles of family history and lifestyle and metabolic risk factors with diabetes risk. Methods: This study included 5290 participants without diabetes at baseline with a mean follow‐up of 4.4 years. Five unhealthy lifestyles and five metabolic disorders were each allocated a score, resulting in an aggregated lifestyle and metabolic risk score ranging from 0 to 5. Eight risk profiles were constructed from combinations of three risk categories: family history of diabetes (yes, no), lifestyle risk (high, low), and metabolic risk (high, low). Results: Compared with the profile without any risk category, other profiles exhibited incrementally higher risks of diabetes with increasing numbers of categories: the hazard ratio (HR, 95% confidence interval [CI]) for diabetes ranged from 1.34 (1.01–1.79) to 2.33 (1.60–3.39) for profiles with one risk category, ranged from 2.42 (1.45–4.04) to 4.18 (2.42–7.21) for profiles with two risk categories, and was 4.59 (2.85–7.39) for the profile with three risk categories. The associations between the numbers of risk categories and diabetes risk were more prominent in women ( p interaction = .025) and slightly more prominent in adults <55 years ( p interaction = .052). Conclusions: This study delineated associations between comprehensive risk profiles with diabetes risk, with stronger associations observed in women and slightly stronger associations in adults younger than 55 years. Abstract : Highlights Compared with the profile without any risk category, of profiles with one risk category, the profile with family history conferred the highest (2.33‐fold) diabetes risk; of profiles with two risk categories, the profile with family history and high lifestyle risk conferred the highest (4.18‐fold) diabetes risk; the profile with all three risk categories conferred 4.59‐fold increased diabetes risk. Associations between the risk category numbers and diabetes were more prominent in women and slightly more prominent in adults <55 years. Integrating comprehensive risk profiles is vital for effective prediction and prevention of diabetes, especially for women and younger adults. 摘要: 背景: 糖尿病家族史, 不健康的生活方式和代谢紊乱分别与较高的糖尿病风险相关, 但这三种风险类别的不同组合如何与糖尿病事件相关仍不清楚。我们旨在评估家族史, 生活方式以及代谢风险因素的综合风险概况与糖尿病风险的相关性。 方法: 这项研究包括5290名基线时无糖尿病的参与者, 平均随访时间为4.4年。对五种不健康的生活方式和五种代谢紊乱分别进行评分, 使生活方式和代谢风险综合评分从0到5不等。根据三个风险类别的组合构建了八个风险类别:糖尿病家族史(是, 否), 生活方式风险(高, 低)和代谢风险(高, 低)。 结果: 与无任何危险类别的相比, 随着危险类别的增加, 患糖尿病的风险逐渐增加:具有一个危险类别的风险比(HR, 95%可信区间[CI])为1.34(1.01 1.79) 2.33(1.60 3.39), 具有两个危险类别的为2.42(1.45 4.04) 4.18(2.42 7.21), 具有三个危险类别的HR为4.59(2.85 7.39)。风险类别的数量与糖尿病风险之间的关联在女性中更加显著(P交互作用 =0.025), 在55岁以下的成年人中略显著(P交互作用 =0.052)。 结论: 这项研究描述了全面的风险特征与糖尿病风险之间的关联, 在女性中观察到更强的关联, 在55岁以下的成年人中观察到略强的关联。